Peningkatan Kemampuan Literasi Siswa Kelas V SD melalui Implementasi Pembelajaran Tematik : Penelitian Tindakan Kelas SDN Citarik III - Bambang Mokhamad Akbar (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to improve the literacy skills of fifth-grade students at SDN Citarik III through the implementation of thematic learning. The method used in this research is Classroom Action Research (CAR), which was conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection. The results of the study showed significant improvement in the students' literacy skills, reflected in the increased literacy test scores and active student involvement in group discussions. The thematic learning approach successfully enhanced students' reading, writing, and critical thinking skills. This improvement was more evident in the second cycle, where the majority of students showed significant progress in their literacy abilities.